Fundamentals of fiber optics - fiber history, applications, and specialty fibers - Johnson, Larry (IEEE, 2009)
The silicon-germanium heterojunction bipolar transistor (SiGe HBT) is the first practical bandgap-engineered device to be realized in silicon. This course will provide a comprehensive review of the state-of-the-art in SiGe HBTs and assess its potential for current and future wireless and wireline applications. SiGe HBT technology combines transistor performance competitive with III-V technologies such as GaAs and InP with the processing maturity, integration levels, yield, and cost commonly associated with conventional Si CMOS fabrication. First-generation SiGe HBTs can deliver: fT in excess of 50 GHz, fmax in excess of 70 GHz, minimum noise figure below 0.5 dB at 2.0 GHz, linearity efficiency (OIP3/Pdc) above 10, 1/f noise corner frequencies below 1 kHz, operation at cryogenic temperatures, excellent radiation hardness, as well as yield, reliability and cost comparable to Si. Aggressively-scaled SiGe HBTs can achieve greater than 200 GHz transistor-level performance, and thus are expected to enable Si-based solutions for >40 GB/sec data links and emerging RF, microwave, and even mm-wave systems